Feeding, fecundity and lifespan in female Drosophila melanogaster. - Barnes, A; Wigby, S; Boone, J; Partridge, L; Chapman, T (2008)
Male seminal fluid proteins induce a profound remodelling of behavioural, physiological and gene signalling pathways in females of many taxa, and typically cause elevated egg production and decreased sexual receptivity. In Drosophila melanogaster, these effects can be mediated by an ejaculate 'sex peptide' (SP), which, in addition, contributes significantly to the cost of mating in females. Recent research has revealed that SP can stimulate female post-copulatory feeding, raising the possibility that the widespread female cost of mating could be due to over-feeding. In this study, we used D. melanogaster as a model to test this hypothesis. We first show that elevated post-mating feeding is dependent upon egg production and does not occur in sterile ovoD1 mutant females. This conclusion was also supported by the increase in feeding of virgin females whose egg production was experimentally elevated. We then demonstrated that sterile ovoD1 and fertile females experienced identical survival costs of mating, related to their frequency of mating and not to female feeding rate or to egg production. We conclude that female mating costs are not the result of over-feeding, but may be due to other, potentially more direct, effects of ejaculate molecules.